2012
DOI: 10.1016/j.jml.2011.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Development of dual-retrieval processes in recall: Learning, forgetting, and reminiscence

Abstract: We investigated the development of dual-retrieval processes with a low-burden paradigm that is suitable for research with children and neurocognitively impaired populations (e.g., older adults with mild cognitive impairment or dementia). Rich quantitative information can be obtained about recollection, reconstruction, and familiarity judgment by defining a Markov model over simple recall tasks like those that are used in clinical neuropsychology batteries. The model measures these processes separately for lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 64 publications
(85 reference statements)
2
27
0
Order By: Relevance
“…The finding that children's ability to behaviorally recall contextual details associated with events increases during early childhood is consistent with several previous studies in school-aged children (Bauer et al, 2012;Cycowicz et al, 2001;Ghetti et al, 2010;Hamond & Fivush, 1991;Riggins, 2014;Riggins et al, 2009aRiggins et al, , 2009bSluzenski et al, 2006; see also, Anooshian, 1999;Anooshian & Seibert, 1996;Billingsley et al, 2002;Brainerd et al, 2004;Brainerd et al, 2012;Friedman et al, 2010;Lloyd et al, 2009;Ghetti & Angelini, 2008;Ghetti et al, 2010). However, findings from the present study extend previous work by documenting that these changes are also accompanied by age-related increases in ERP amplitude late in the ERP response (i.e., between 800 and 1,000 ms) between 3 and 4 years of age, which suggests that the increase at the behavioral level may be due to increased resources at the neural level.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The finding that children's ability to behaviorally recall contextual details associated with events increases during early childhood is consistent with several previous studies in school-aged children (Bauer et al, 2012;Cycowicz et al, 2001;Ghetti et al, 2010;Hamond & Fivush, 1991;Riggins, 2014;Riggins et al, 2009aRiggins et al, , 2009bSluzenski et al, 2006; see also, Anooshian, 1999;Anooshian & Seibert, 1996;Billingsley et al, 2002;Brainerd et al, 2004;Brainerd et al, 2012;Friedman et al, 2010;Lloyd et al, 2009;Ghetti & Angelini, 2008;Ghetti et al, 2010). However, findings from the present study extend previous work by documenting that these changes are also accompanied by age-related increases in ERP amplitude late in the ERP response (i.e., between 800 and 1,000 ms) between 3 and 4 years of age, which suggests that the increase at the behavioral level may be due to increased resources at the neural level.…”
Section: Discussionsupporting
confidence: 91%
“…Novel paradigms (using behavioral, electrophysiological, or neuroimaging techniques) that allow for the distinction of these memory processes in early childhood are greatly needed and represent an important area for further research. Moreover, future studies should investigate whether similar memory networks are engaged at multiple developmental stages (e.g., infancy and early childhood; see Mecklinger et al., , for findings in school‐aged children and adolescents), as well as how long and under what conditions developmental changes are apparent (e.g., Brainerd et al., ; Friedman et al., ). Results from the present study represent an initial attempt to begin to distinguish age‐related differences in cognitive and neural processes supporting memory in early childhood, which is an important and necessary element to understanding the development of memory in general.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies now suggest the existence of different developmental trajectories for the different components of episodic memory. In particular, recent studies have shown that familiarity-based processes develop earlier than recollection-based ones (Billingsley et al, 2002 ; Ghetti and Angelini, 2008 ; Brainerd et al, 2012 ). Research has also shown that recalling contextual information develops later than recalling the information itself (Cycowicz et al, 2001 , 2003 ; Pirogovsky et al, 2006 ).…”
Section: Typically Developing Childrenmentioning
confidence: 99%
“…With remember/know, for instance, subjects must read and comprehend complex instructions telling them how to introspect on their mental states, and they must implement those instructions accurately on recognition tests. Ghetti, Mirandola, Angelini, Cornoldi, and Ciaramelli (2008; cited in Ghetti, 2008) found that children could not follow even simplified versions of these instructions, and similar problems have been reported in studies of impaired older adults (Brainerd, Aydin, & Reyna, 2012). …”
Section: Dual-process Conceptions Of Recognition and Recallmentioning
confidence: 60%